Persepsi Penyedia dan Pemakai Laporan Keuangan Terhadap Pengungkapan Biaya Riset dan Pengembangan - Nur Sayidah (Jurnal Akuntansi dan Auditing Indonesia, 2004)
The main purpose of this study is to examine the cost and benefit on disclosures of the research and development (R&D) costs by comparing the perceptions of financial managers (prepares of financial statement) and financial analysts (users of financial statement). Stated hypotheses to examine were: first, differences of the perceived net cost or net benefit of disclos¬ing research and development expenditures both mandatory disclosures or voluntary disclosures. Second, perceptions’ differences on the magnitude of costs/disadvantages which constrain R & D costs disclosures.Data collection was carried out by a questionare survey. Respondents are financial managers from manufacturing firms and financials analysts from security houses. The method were used to test the stated hypotheses is t-test.The result shows that:  first, there are no significant differences in the perceptions of fi¬nancial managers and financial analysts about net benefit or net cost of disclosing R & D costs. Second, there are significant differences in the perceptions of financial managers and financial analysts about magnitude of collecting and processing cost and auditing cost. Keywords: disclosure, research and development costs, net benefit, net cost